Patients’ compliance to clinical treatment that benefit from the Brazilian National Glaucoma Program - Araújo,Tiago de Assis Clemente de (2020)
Abstract Objective: To evaluate the adherence to clinical glaucoma treatment in patients that benefit from the Brazilian National Glaucoma Program and receive antiglaucomatous eye drops free of charge. Methods: This cross-sectional study included 255 patients that benefit from the Brazilian National Glaucoma Program (BNGP) and were assisted at the Altino Ventura Foundation (FAV), Pernambuco state, Brazil. The Morisky’s Adhesion Scale (MAS) was used to evaluate adhesion profile to treatment. Patients with a Morisky’s Adhesion score ≥ 6 was considered adherent to treatment. The analyzed variables included sex, educational level, distance from home to the treatment center, number of eye drops used, time since the glaucoma diagnosis, patients’ subjective classification of their quality of vision, and prevalence of other comorbidities. Results: A total of 255 patients [167 (65.4%) females] were included in this study with a mean age was 65.9 ± 13.8 years (range, 11-99 years). Adherence to clinical glaucoma treatment was seen in 155 patients (60.8%). Worse adherence to treatment was observed in female patients (p=0.034), with low education level (p=0.046), who presented other comorbidities (p=0.048), living in remote areas (p=0.038), judged their vision as satisfactory (p=0.046), and who were recently diagnosed with glaucoma (p=0.001). Conclusion: 40% of patients who benefited from the Brazilian National Glaucoma Program were not compliant to treatment. Low adhesion rate was mostly seen in female patients, socially vulnerable, living in remote areas, recently diagnosed with glaucoma, using fewer eyedrops, presenting other comorbidities, and in those that considering themselves of having a satisfactory vision.